2014
DOI: 10.1039/c4py00473f
|View full text |Cite
|
Sign up to set email alerts
|

Diels–Alder crosslinked HA/PEG hydrogels with high elasticity and fatigue resistance for cell encapsulation and articular cartilage tissue repair

Abstract: The gelation time of Diels–Alder crosslinked HA/PEG hydrogels can be reduced to an appropriate level for cell encapsulation and survival. At the same time, the DA click reaction makes the gel highly resilient and resistant to cyclic compression loading, which biomimics native articular cartilage biomechanical functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 52 publications
2
66
0
Order By: Relevance
“…The gelation kinetics of many bio-orthogonal chemistries are not conducive to cell encapsulation. For instance, Diels–Alder reactions between furan and maleimide moieties result in gelation times ranging from tens to hundreds of minutes, [13,15,16] which is too slow to achieve homogeneous cell dispersion within the gel and can result in decreased cell viability. [15] On the other hand, the reaction between tetrazines and trans -cyclooctenes proceeds too rapidly to achieve uniform gelation and cell encapsulation by simple mixing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gelation kinetics of many bio-orthogonal chemistries are not conducive to cell encapsulation. For instance, Diels–Alder reactions between furan and maleimide moieties result in gelation times ranging from tens to hundreds of minutes, [13,15,16] which is too slow to achieve homogeneous cell dispersion within the gel and can result in decreased cell viability. [15] On the other hand, the reaction between tetrazines and trans -cyclooctenes proceeds too rapidly to achieve uniform gelation and cell encapsulation by simple mixing.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Diels–Alder reactions between furan and maleimide moieties result in gelation times ranging from tens to hundreds of minutes, [13,15,16] which is too slow to achieve homogeneous cell dispersion within the gel and can result in decreased cell viability. [15] On the other hand, the reaction between tetrazines and trans -cyclooctenes proceeds too rapidly to achieve uniform gelation and cell encapsulation by simple mixing. [19] Synthetic polymers, such as PEG, are bio-inert and must be further functionalized to permit biological functions such as cell adhesion [20] and proteolytic degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels are desirable biomaterials for tissue engineering because of high water content, good mechanical property, promising biocompatibility and high permeability to oxygen, nutrients and other water-soluble metabolites [26,27]. For obtaining appropriate mechanical properties and stable metabolic characterizations, a variety of chemical crosslinking methods and crosslinking agents have been developed to produce amphiphilic and gel-like HA materials by forming covalent networks [1], such as photo polymerization [28], Michael-type addition reaction [29], Schiff-base reaction [30], thiolene reaction [31], oxidizing reaction of tyramine [32,33] and other reactive groups [34,35]. Although these methods could effectively prepare HA derivatives hydrogels for application in biomedicine field, it still remained some problems for researchers to dissolve, such as the exogenous cytotoxicity derived from the additive initiator, crosslinking agents or byproducts and poor gelation efficiency due to use of light, radiation to initiate the crosslinking reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, very few authors reported direct encapsulation of cells in the gels using the Diels-Alder strategy. This may be attributed to rather long gelation time (> 50 min) [70]. Another limitation could arise from the reactivity of maleimide towards thiol-containing biomolecules in vivo, undergoing Michael-type 1,4-addition yielding thioether ligation products.…”
Section: Diels-alder Cycloadditionmentioning
confidence: 99%